Task-Based Language Teaching (TBLT) in Arabic Learning: A Practical Framework for Classroom Application - Aisha Rahman (IJAS: International Journal of Arabic Studies, 2025)
This This study examines the effectiveness of Task-Based Language Teaching (TBLT) in enhancing Arabic language proficiency, particularly speaking skills. The research involved implementing TBLT strategies in classroom instruction, focusing on communicative tasks such as role-playing, problem-solving, and storytelling. Data were collected through pre-test and post-test assessments, classroom observations, and student and teacher feedback. The results demonstrated a significant improvement in students’ fluency, accuracy, and vocabulary usage. Statistical analysis revealed a notable increase in post-test scores, while qualitative findings indicated positive student engagement and motivation. Teachers also reported increased student participation but faced challenges in task design and classroom management. Despite these challenges, TBLT proved to be an effective pedagogical approach in fostering communicative competence in Arabic learning. The study highlights the need for structured task sequences, adequate teacher training, and the development of Arabic-specific TBLT materials to optimize its implementation in various learning contexts